The prospect and challenges of sodium‐ion batteries for low‐temperature conditions. Issue 3 (20th June 2022) - Wang, Meng; Wang, Qianchen; Ding, Xiangyu; Wang, Yingshuai; Xin, Yuhang; Singh, Preetam; Wu, Feng; Gao, Hongcai
Abstract: In recent years, considerable attention has been focused on the development of sodium‐ion batteries (SIBs) because of the natural abundance of raw materials and the possibility of low cost, which can alleviate the concerns of the limited lithium resources and the increasing cost of lithium‐ion batteries. With the growing demand for reliable electric energy storage devices, requirements have been proposed to further increase the comprehensive performance of SIBs. Especially, the low‐temperature tolerance has become an urgent technical obstacle in the practical application of SIBs, because the low operating temperature will lead to sluggish electrochemical reaction kinetics and unstable interfacial reactions, which will deteriorate the performance and even cause safety issues. On the basis of the charge‐storage mechanism of SIBs, optimization of the composition and structure of electrolyte and electrode materials is crucial to building SIBs with high performance at low temperatures. In this review, the recent research progress and challenges were systematically summarized in terms of electrolytes and cathode and anode materials for SIBs operating at low temperatures. The typical full‐cell configurations of SIBs at low temperatures were introduced to shed light on the fundamental research and the exploitation of SIBs with high performance for practical applications. Abstract : A systematic evaluation of the recent research progress and the application of key materials for sodium‐ion batteries (SIBs) operating at low temperatures has been provided in this review, with a special focus on the functionalization of electrolyte and electrode materials and the representative Na‐ion full‐cell configurations. The challenges and possible strategies to improve the performance of SIBs at low temperatures are discussed in detail, aiming to facilitate the application of SIBs in a wide range of fields.